Pengaruh Board Size dan Faktor Lainnya terhadap Audit Quality - Callista, Angela; Wijaya, Novia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this research is to get empirical evidence from the seven variables used in the research. This study examines seven independent variables, namely audit fee, audit tenure, auditor’s reputation, audit rotation, auditor specialization, board size and audit committee on the dependent variable, namely audit quality.The population in this study were companies in the consumer cyclicals and consumer non-cyclicals sector that were listed in Indonesia Stock Exchange (IDX) on 2016-2022 with the secondary data collection method using purposive sampling method. The Sample used in this study were 144 samples consists of 48 companies.The research finding can be summarized as follows. One variable has an effect on audit quality, auditor specialization, meanwhile the others such as, audit fee, audit tenure, auditor’s reputation, audit rotation, board size and audit committee do not have any effect on audit quality.